Management of institution of secondary education on the basis of leadership paradigm - Lynov Konstantin (Borys Grinchenko Kyiv Metropolitan University, 2016)
The author states that during the last century understanding of the phenomenon of leadership has changed rapidly, appearing new meanings and approaches. Those theories that arose identified leadership with the personality of the leader, or with social process. It is noted that in recent decades, scientists engaged in trying to integrate the two approaches, especially in education, where manifestation of leadership required providing both from the principal and from the teacher, the student, where it contributes the specificity of institution of secondary education. It is emphasized that social transformations generate the need for new management paradigm that is associated with changes both in educational institutions and in society in general. The object of transformation is not just an employee but a creative person with his needs in self-expression, self-realization, considering its interests and points of view. Leadership creates overall team culture in educational institutions on the basis of jointly produced vision and shared values. Just in triangle «leader - followers - management process» actualized need in leadership skills, competencies and behaviours development not only leader but followers too, and team interaction at school. Necessary changes in institution of secondary education based on personal, human and professional values. Based on this values head-leader begins the process of creation of the Concept of institution of secondary education, which is a powerful tool in the work of school staff, aimed at determining the idea of an educational institution, its understanding of the place in society. The author offers his own point of view on the management of school which is implemented on the basis of leadership and distinguishes success criteria for institution of secondary education activity and for its leader.